Behavior of maize weevil at doses of permethrin - Silva, Luciana Barboza; Silva, Leonardo Santana; Mancin, Adriana Cristina; Carvalho, Gabriel Santos; Silva, Jorlan Cardoso; Andrade, Lígia Helena (Comunicata Scientiae, 2013)
The maize weevil, Sitophilus zeamais Motsch. (Coleoptera: Curculionidae), is among the most destructive and globally well distributed pests of stored grain; the main method of control is the use of insecticides. This study aimed to compare, under laboratory conditions (27±2°C, 70%±10% RH, LD 12:12), the behavior of maize weevil populations exposed to different doses of the insecticide permethrin. Dose-response bioassays were conducted to determine CL50 values. Instantaneous rate of population growth, maize grain consumption and insect body mass were also determined at different permethrin concentrations. Insects were submitted to preference bioassays comparing permethrin-treated (insecticide residue) and untreated surfaces. Among the populations of Sitophilus zeamais used in bioassays, the population with the highest CL50 value was that of Palmeira, PI (127.7 µg i.a./cm2); the population with the lowest CL50 value was that of Balsas, MA (27.0 µg i.a./ cm2). Significant differences were observed among the permethrin concentrations with respect to instantaneous rate of population growth, consumption of dry maize grain biomass, insect body mass and number of adults emerged after 100 days. Regarding the behavior of S. zeamais adults, there was not significant discrimination in relation to the majority of concentrations; however, when compared to control, the proportion of individual insects that rejected the treated area was significant.